2006
DOI: 10.1111/j.1096-3642.2006.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

A new divergent lineage of Daphnia (Cladocera: Anomopoda) and its morphological and genetical differentiation from Daphnia curvirostris Eylmann, 1887

Abstract: The systematic biology of the subgenus Daphnia s . s . remains confused. Prior attempts at resolution used chiefly postabdominal claw morphology, chromosome numbers and rRNA gene sequences as characters for higher-level relations. Still, several taxa, such as Daphnia curvirostris Eylmann, 1878, have unclear affiliations. We addressed the position of D. curvirostris in this genus by estimating phylogenetic trees from a rapidly evolving protein coding gene (ND2), conducting broad geographical comparisons and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…As previous studies showed that D. cucullata and D. longispina were closely related species to D. rosea s.l. in the mitochondrial ND2 phylogeny [35], we used these species as outgroups [see Additional file 4]. All samples were preserved in absolute ethanol at room temperature, or frozen at -80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies showed that D. cucullata and D. longispina were closely related species to D. rosea s.l. in the mitochondrial ND2 phylogeny [35], we used these species as outgroups [see Additional file 4]. All samples were preserved in absolute ethanol at room temperature, or frozen at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…A c . 1000 bp fragment of the mitochondrial protein-coding NADH-2 (ND2) gene was amplified using the primers MetF3 (5'-GTT CAT GCC CCA TTT ATA GGT TA-3') and TrpR (5'-GAA GGT TTT TAG TTT AGT TAA CTT AAA ATT CT-3') [35]. A c .…”
Section: Methodsmentioning
confidence: 99%
“…However, genetic studies have demonstrated the presence of specimens belonging to a "non-European" species similar to D. longispina in Japan, but have not revealed specimens of D. longispina s. str. in Japan (Ishida et al 2006;Ishida 2007). In Japan, specimens attributed to D. schmackeri probably are D. dentifera Forbes, 1893, a common pelagic species (Ishida 2007 Comments.…”
Section: Daphnia {Daphnia) Curvirostris Insulana Richard 1895mentioning
confidence: 99%
“…Atomic P:C ratios of HIP and LOP algae were measured by the method described in Iwabuchi and Urabe (submitted ), and were 7.9 3 10 À3 and 1.2 3 10 À3 , respectively. D. tanakai (Ishida et al 2006) was collected from a marsh in Mt. Zao, Miyagi, Japan.…”
Section: Algal Food and Animalsmentioning
confidence: 99%